Impact of the US-China Trade War on Foreign Trade of Emerging Economies: Brazil, South Africa, and Indonesia - Kurniawan, Andi; Rizal Luthfi, Khoirur (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2023)
The study analyses the potential impacts of the US-China trade war on the foreign trade of emerging economies, i.e., Indonesia, Brazil, and South Africa, and their foreign economic policies to obtain alternative markets outside the US and China. These countries were chosen because they have similar industrial characteristics and robust commercial relationships with the US and China. This study uses desk review approach and secondary data analysis from the International Trade Center (ITC) Database, the WTO Tariff Database, and the Peterson Institute of International Economics (PIIE). The impacts were portrayed in several views: triangular trade structure, global value chain, China+1, and Global South relationship. In the context of a triangular trade structure with China as the mediator, Indonesia’s and Brazil's trade was relatively secure since they exported considerable natural resources to China. At the same time, they could maintain positive trade performance with the US and China owing to the global value chain. South Africa has extensive imports of intermediate goods from the US and China, mainly for the automotive sector and further processed for the African market. However, since the significant position of the US as a trading partner, Indonesia, Brazil, and South Africa were potentially exposed to protectionism behavior. Indonesia benefits significantly from the US General System Preferences (GSP) trade facilities for developing countries. The consistent trade surplus has raised critical concerns from the US government regarding Indonesian exports. Therefore, the escalation has also enhanced cooperation in the Global South, including the Brazil-led Mercosur free trade negotiation with Singapore and Indonesia's preferential trade agreement with Pakistan and Bangladesh.